Covid-19 and the impacts on mental health: a narrative literature review study - Pavani, Fabiane Machado (2020)
ABSTRACTObjective: To identify the repercussions on mental health of groups and populations in the context of the new coronavirus pandemic.Method: Narrative review care out in three databases, in March 2020, using the descriptors mental health and coronavirus. A total of 19 publications were analyzed, organized in a synoptic table, containing type of publication, authors, country, sample, objective and main results. From this analysis, two thematic axes emerged: identification of problems and vulnerable groups in mental health; and mental health interventions and actions.Results: The first axis showed manifestations of suffering - anguish, insomnia, anger, stress, fear. The second revealed the need to build government policies and general guidelines; production of information and communication; and mental health care practices.Conclusions: The repercussions on mental health in the population intensified with the pandemic, identifying vulnerable groups, and the need to build coping strategies and policies aimed at mental health during epidemics. Keywords: Coronavirus infections. Mental health. Coronavirus. Pandemics. Mental health services